Co9S8 nanoparticles anchored on nitrogen and sulfur dual-doped carbon nanosheets as highly efficient bifunctional electrocatalyst for oxygen evolution and reduction reactions. Issue 34 (15th August 2017) - Wu, Can; Zhang, Yuhang; Dong, Duo; Xie, Haiming; Li, Jinghong
Abstract : Co9 S8 /N, S–C nanosheets were prepared using an NaCl-templated strategy, and exhibited excellent OER and ORR catalytic performance. Abstract : To promote the practical application of electrochemical energy storage and conversion systems, nonprecious electrocatalysts of low cost and with highly efficient performance in oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are highly desired. In this work, a cubic sodium chloride (NaCl) crystal-templated strategy is proposed for coupling Co9 S8 nanoparticles to nitrogen- and sulfur-doped carbon nanosheets (Co9 S8 /N, S-CNS) by facile pyrolysis. The nitrogen and sulfur dual-doped carbon nanosheets can effectively prevent the aggregation of Co9 S8 nanoparticles and greatly improve the conductivity of the hybrid structure. The well-dispersed Co9 S8 nanoparticles could provide more active sites. When evaluated as a bifunctional electrocatalyst, an overpotential of 350 mV could yield 10 mA cm −2 current density for OER and a high onset potential around 0.90 V vs. RHE was obtained with a four-electron pathway for ORR, which is comparable to that of a Pt/C catalyst. The remarkable electrochemical performance can be attributed to the synergistic catalytic effect of Co9 S8 nanoparticles and the N, S-doped carbon nanosheets. Considering the simplicity, low cost and scalability of the approach, the strategy presented here can be extendable to the preparation of other nanoparticles/carbon hybrid nanosheets, which may potentially be applied in the fields of high-performance supercapacitors, lithium-ion batteries, catalysts, sensors, adsorbents and so on.